The Diagnostic Value of Plasma miRNA-497, cTnI, FABP3 and GPBB in Pediatric Sepsis Complicated with Myocardial Injury - Huang C; Xiao S; Xia Z; Cheng Y; Li Y; Tang W; Shi B; Qin C; Xu H (Dove Medical Press, 2021)
Chengjiao Huang,* Shuna Xiao,* Zhi Xia, Ying Cheng, Yong Li, Wen Tang, Buyun Shi, Chenguang Qin, Hui Xu Department of PICU, Maternal and Child Health Hospital of Hubei Province (Women and Children’s Hospital of Hubei Province), Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hui XuDepartment of PICU, Maternal and Child Health Care Hospital of Hubei Province, No. 745 Wuluo Road, Hongshan District, Wuhan, Hubei, 430070, People’s Republic of ChinaTel +86-027-87169353Email hbsfy2020picu@163.comObjective: To investigate the diagnostic value of plasma miRNA-497, cardiac troponin I (cTnI), fatty acid binding protein 3 (FABP3), glycogen phosphorylase isoenzyme BB (GPBB) in pediatric sepsis complicated with myocardial injury.Methods: From August 2018 to February 2020, 82 children with sepsis admitted to our hospital and 50 health children who came for physical examination (defined as control group) were enrolled in this study. Children with sepsis and myocardial injury were enrolled in the combined group (n=35), and those without myocardial injury were enrolled in the sepsis group (n=47). General data of three groups were collected, and the levels of miRNA-497, FABP3, GPBB, creatine kinase isoenzyme MB (CK-MB), procalcitonin (PCT), C-reactive protein (CRP), cTnI and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were detected and the cardiac function was measured. The diagnostic value of plasma miRNA-497, cTnI, FABP3 and GPBB in pediatric sepsis complicated with myocardial injury was analyzed.Results: The infection site of the combined group was not significantly different from that of the sepsis group. The levels of miRNA-497, FABP3, GPBB, CK-MB, PCT, CRP, cTnI, NT-proBNP in the combined group were all higher than those in the sepsis group and the control group (P< 0.05), and the left ventricular ejection fraction (LVEF) in the combined group was significantly lower than that in the other two group (P< 0.05). The area under the curve (AUC) of the combination of miRNA-497, FABP3, GPBB, and cTnI in the diagnosis of sepsis complicated with myocardial injury was significantly higher than that of CK-MB, PCT, CRP, NT-proBNP alone (P< 0.05), but there was no significant difference when compared with miRNA-497, FABP3, GPBB and cTnI alone (P> 0.05). When the optimal thresholds of miRNA-497, FABP3, GPBB, and cTnI were set to 2.03, 6.23ng/mL, 4.01ng/mL, 1.23ng/mL, respectively, the sensitivity was 95.65%, 88.89%, 82.61%, 87.50%, respectively; the specificity was 83.33%, 94.12%, 83.33%, 90.91%, respectively; and the accuracy was 91.43%, 91.43%, 82.86%, 88.57%, respectively. Pearson correlation analysis indicating that miRNA-497 was positively correlated with the levels of FABP3, GPBB, and cTnI in the combined group (r=0.821, 0.621, 0.782, P< 0.05).Conclusion: Plasma miRNA-497, cTnI, FABP3, and GPBB levels were increased in pediatric sepsis complicated with myocardial injury, and their combination had high diagnostic value, which was of great clinical significance for early diagnosis and early treatment of pediatric sepsis complicated with myocardial injury.Keywords: miRNA-497, cTnI, FABP3, GPBB, pediatric sepsis, myocardial injury, diagnosis